New buffer bloat mitigation alternatives: infrastructure versus congestion control - Popovsky, Alejandro Daniel (2016)
This paper studies the use of Palermo receiver side congestion control as an alternative to Active Queue Management (AQM) for end users needing to improve latency and fair sharing in their incoming traffic. Because of the end users lacking administrative access to ISP devices in order to tune their incoming bottleneck queue, this alternative results in a valid option to increase performance.